1998
DOI: 10.1046/j.1365-3156.1998.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

The early sporogonic cycle of Plasmodium falciparum in laboratory‐infected Anopheles gambiae: an estimation of parasite efficacy

Abstract: SummaryThis study investigated the successive losses in the parasite densities of Plasmodium falciparum stages during the early sporogony in laboratory-reared Anopheles gambiae infected by membrane feeding with blood from naturally infected gametocyte carriers (Ͼ50 gametocytes/mm 3 ). The developmental stages of P. falciparum in the mosquito were studied from zygote to oocyst, by immunofluorescent method using monoclonal antibodies against the Pfs25 protein present on the surface of newly formed gametes. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 29 publications
(36 reference statements)
0
55
1
Order By: Relevance
“…This percentage is slightly higher than those found in similar studies (53% in Burkina Faso; 7 38% or 62% in Cameroon; 8,10 45% in Papua New Guinea). 15 This difference may be related to the large proportion of recent malaria attacks in our gametocyte carrier sample.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…This percentage is slightly higher than those found in similar studies (53% in Burkina Faso; 7 38% or 62% in Cameroon; 8,10 45% in Papua New Guinea). 15 This difference may be related to the large proportion of recent malaria attacks in our gametocyte carrier sample.…”
Section: Discussioncontrasting
confidence: 64%
“…The results have two implications: first, studies of experimental infections performed by membrane feeding [7][8][9][10] and by direct feeding [11][12][13] have epidemiological relevance and second, trials to evaluate the efficacy of a transmission-blocking vaccine can use either method. Volunteers appear to favor providing blood by venipuncture for the membrane feeding method rather than directly to mosquitoes feeding on their skins.…”
Section: Discussionmentioning
confidence: 99%
“…Recent detailed laboratory-based analysis of the population dynamics of avian, murine and human malaria parasites in different vector species has identified a strong developmental bottleneck during the transition of ookinetes to oocysts coinciding with the transition of the parasite through the midgut epithelium (2). This bottleneck was also observed by using field isolates of Plasmodium falciparum (3).…”
mentioning
confidence: 96%
“…Several studies with rodent and human malaria parasites have revealed that the ookinete-to-oocyst transition is the most vulnerable link in sporogonic development of malaria parasites (1)(2)(3). Thus, the developing parasite stages in the mosquito midgut provide an ideal target for transmission-blocking vaccines.…”
mentioning
confidence: 99%